The effect of pharmaceutical interventions on parenteral nutrition in a neonatal intensive care unit 5 years after the introduction of electronic prescribing. Issue 2 (12th March 2012) - Brito, R.; Costa, C.; Oliveira, M.; Teixeira, S.; Almeida, P.
Abstract : Background: Parenteral nutrition (PN) prescriptions are not error-free regarding calculations. The errors are more important the more premature the patient. Electronic prescribing aims to automate the process and therefore reduce errors, helping the pharmacist to validate the prescriptions. Purpose: To assess the impact of electronic prescribing (for PN) in the neonatal intensive care unit, comparing the year prior to computerisation to the fifth year after, in order to improve the prescription tool. Materials and methods: All PN prescriptions in the year before computerisation (2347) and the fifth year after (2155), were reviewed and the following parameters compared concerning prescribing errors: calcium/phosphorus relation (Ca/P relation), final volume (when the final volume is smaller than the sum of all components), osmolarity, phosphorous prescription (source: sodium glycerophosphate) when sodium is not wanted in the parenteral nutrition solution (phosphorous without sodium) and omission of nutrients. Results: There was a decrease in prescribing error in three parameters: Ca/P relation (−10.0%), osmolarity (−97.2%) and final volume (−66.7%). However there was an increased error in the PN prescription of phosphorous introducing unwanted sodium (236.4%) and omission of nutrients (35.3%). Conclusions: The use of electronic prescribing for PN has contributed to error reduction and simplified the process. Moreover it was possible to evaluate the prescription tool parameters that need to be improved (phosphorous prescription).